Phlebotomine in urban foci of Visceral and American Cutaneous Leishmaniases in a municipality in the Brazilian Northeast - Silva, Mauriely Paiva de Alcântara e; Sousa , Raimundo Leoberto Torres de; Vasconcelos, Sílvia Alcântara; Mendonça , Vagner José (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: The Visceral and American Cutaneous Leishmaniases are a public health problem in the Americas, in the municipality of Altos, state of Piauí, are considered endemic. Aim: To carry out a faunal survey of the phlebotomine species in the areas of transmission of visceral and cutaneous, both human and canine, leishmaniases, in the municipality of Altos, Piauí. Outlining: It was carried out through entomological survey, it encompassed capture, separation, identification, and analysis of phlebotomine species in determined regions in the municipality of Altos, Piauí, between August 2017 and July 2019. Results: The most found species was Lutzomyia longipalpis, with 1,399 sandflies captured, 1,299 males and 140 females. Some other species were also found, such as Nyssomyia whitmani, Lutzomyia dispar, Evandromyia evandroi. Implications: The research helps to provide data that can contribute to the formulation of surveillance and control actions for these vectors, enabling responsible entities to develop public policies to control leishmaniasis.